PENINGKATAN PEMAHAMAN BUDAYA KESELAMATAN DAN KESEHATAN KERJA MELALUI SOSIALISASI IMPLEMENTASI POSTUR KERJA ERGONOMIS - Sido Dea Auvia; Ibnu Abdul Rosid; Cici Financia (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2025)
This community service activity aims to increase the understanding of SMK Muhammadiyah Berbah students about the importance of applying ergonomic work postures in learning activities and work practices. Through socialization and training, students are expected to identify the risk of injury due to improper work postures and apply ergonomic principles in their daily activities. Thus, students can maintain personal health and safety and improve the quality of learning and work productivity. The results of this community service journal found that there was an increase in “Keselamatan dan Kesehatan Kerja (K3)” knowledge among SMK Muhammadiyah Berbah students and a significant increase in scores for both genders, with males showing a slightly higher average increase than females. The conclusion from the implementation of these activities is that an increase in knowledge is obtained and efforts to produce students who have competence in the effect of gaining knowledge related to posture at work on long-term occupational health are proven to increase.